2005
DOI: 10.1071/en05072
|View full text |Cite
|
Sign up to set email alerts
|

Marine Organic Halide and Isoprene Emissions Near Mace Head, Ireland

Abstract: Environmental Context.Atmospheric aerosols have received increasing attention, not only because they include cloud condensation nuclei, essential for precipitation, but also because of their absorption and scattering of radiation, which may affect climate. The process of aerosol formation, however, is not well understood. This paper describes measurements of the fluxes into the atmosphere of several possible biogenic precursors to primary aerosol production. Abstract.Vertical profiles of the concentration of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Similar flux values (8.8×10 8 molecules cm −2 s −1 ) were estimated at a nearby site by Greenberg et al (2005). They also measured isoprene air concentrations of 10-160 ppt (median 68 ppt), 7-210 ppt (median 63 ppt), and 7-270 ppt (median 41 ppt) at altitudes of 0 m, 50 m, and 100 m, respectively, at the coast 5 km away from Mace Head.…”
Section: Origin and Fate Of Marine Secondary Organic Compoundssupporting
confidence: 52%
“…Similar flux values (8.8×10 8 molecules cm −2 s −1 ) were estimated at a nearby site by Greenberg et al (2005). They also measured isoprene air concentrations of 10-160 ppt (median 68 ppt), 7-210 ppt (median 63 ppt), and 7-270 ppt (median 41 ppt) at altitudes of 0 m, 50 m, and 100 m, respectively, at the coast 5 km away from Mace Head.…”
Section: Origin and Fate Of Marine Secondary Organic Compoundssupporting
confidence: 52%
“…The transfer of iodine from the oceans to the atmosphere, and further to the terrestrial environment, is thought to occur primarily through the emission of organic iodine hydrocarbon from the seawater [49]. These volatile organic iodine species were also suggested to contribute to ozone depletions in the lower stratosphere, particularly the marine boundary layer [50][51] and cloud condensation in the lower troposphere [52]. In fresh water, such as rivers, lakes and rain, iodine exists also as iodide, iodate and organic iodine, but the relative concentration of organic iodine is higher compared to seawater [53][54][55][56].…”
Section: Speciation Of Iodine In Watermentioning
confidence: 99%
“…They suggested that isoprene was a probable precursor to SOA. In situ (Greenberg et al 2005) and remote-sensing studies (Palmer & Shaw 2005) estimated isoprene fluxes ranging from 10 7 to 10 9 molecules cm K2 s K1 from marine biota which could account for a significant source of SOA. Chamber estimates of the aerosol yield of isoprene are of the order of 1-3% depending on the oxidation conditions (Kroll et al 2005(Kroll et al , 2006.…”
Section: Secondary Organic Aerosol Formationmentioning
confidence: 99%